Ca–Mg-Doped Surface-Modified Nano-Sized Ferrihydrite Powder Synthesized by Surfactant Mediation–Precipitation Technique: A Novel Super Adsorbent for Cations - M. Mohapatra; T. Padhi; S. Anand; B.K. Mishra (Adsorption Science & Technology)
In this study, high surface area (312 m 2 g −1 ) nano-sized Ca–Mg-doped ferrihydrite was synthesized using surfactant mediation–precipitation technique. The micrographs obtained by transmission electron microscopy confirmed the particle size to be in the range of 2–5 nm. The weak crystalline nature of powder was indicated by the selected area electron diffraction pattern. Here, we studied the adsorption of four cations [Pb(II), Cd(II), Cu(II) and Co(II)] onto self-prepared nano-sized powder under various experimental conditions. The contact time data followed pseudo-second-order kinetics model for all the four cations giving regression coefficient values >0.99. The isothermic data fitted well to both Langmuir and Freundlich models for Pb(II), Cd(II) and Cu(II) with corresponding Langmuir monolayer capacities of 312.5, 333.3 and 333.3 mg g −1 , respectively. For Co(II) isothermic data, only Freundlich model showed good fit and the experimentally obtained maximum loading capacity was 225 mg g −1 . Desorption studies confirmed that Pb(II)- or Cd(II)-loaded adsorbent can be regenerated/reused. Studies up to five cycles of adsorption–desorption confirmed increase in uptake capacity upon regeneration. Although Cu(II)- or Co(II)-loaded adsorbents could not be regenerated, toxicity characteristic leaching procedure tests confirmed that they were safe for disposal. This is the first study of its kind to report high-loading capacities for various cations and an increase in Pb(II) or Cd(II) uptake capacities after regeneration on an adsorbent. Therefore, the prepared sample can be regarded as a super adsorbent .